Interpreting the synergistic effect in combined ultrasonication-ozonation sewage sludge pre-treatment - Tian, Xinbo (2015)
The sequential combination of ultrasonication and ozonation as sewage sludge treatment prior to anaerobic digestion was investigated. Synergistic volatile suspended solids (VSS) solubilization was observed when low energy ultrasonication (<12 kJ g−1 TS) was followed by ozonation. 0.048 g O3 g−1 TS ozonation induced the maximum VSS solubilization of 41.3% when the sludge was pre-ultrasonicated at 9 kJ g−1 TS; while, the same ozone dosage applied without prior ultrasonication only induced 21.1% VSS solubilization. High molecular weight (MW) components (MW > 500 kDa) were found to be the main solubilization products when sludge was only ozonated. However, solubilization products by ozone were mainly in the form of low MW components (MW < 27 kDa) when sludge was pre-ultrasonicated. The high MW products generated by ultrasound were effectively degraded in the subsequent ozonation. Anaerobic biodegradability increased by 34.7% when ultrasonication (9 kJ g−1 TS) and ozonation (0.036 g O3 g−1 TS) were combined sequentially. The maximum methane production rate increased from 3.53 to 4.32, 4.21 and 4.54 mL CH4 d−1 after ultrasonication, ozonation and ultrasonication–ozonation pre-treatments, respectively.